Hubungan Antara Dukungan Keluarga Dengan Intensi Berhenti Merokok Pada Perokok Aktif - Herawati, Atika, Susatyo Yuwono ,S. Psi, M. Si., Psi (2017)
The behavior of smoking are so easy meet in a various places, like a government places, public places and also school even it places of educating. Habit of smoking behaviour beginning from teenagers. Many all of them we meet in public places is a teenagers. This research aims to know the relationship between family support with intention smoking cessation in smokers. The proposed hypothesis that is there is a positive relationship between family support with intention smoking cessation in smokers. The sampling techniques used in this research is by either using a study population, techniques with the subject of 126 active smokersStudent SMK SaktiGemolongin cases of violations of the smoking in BK. These studies use quantitative methods with the use of a tool to measure the scale of family support and scale intention quit smoking. Based on the results of the analysis of the data obtained coefficient correlation r = 0.892 with significance = 0000 (p < 0.01) which means there is a very significant positive relationship between family support with intention quit smoking. The effective contribution of these two variables is indicated by the value of R ² = 0.892 which means that the variable family support influencing variables intensi quit smoking of 79.5% and 20.5% is affected by other factors. Family support belongs to the empirical average lower with (RE) sebesar88 .05 and average hipotetik (RH) of 82.5. While the intensi quit smoking belongs with the empirical mean (RE) .2 the mean hipotetik and sebesar70 (RH) of 60. Keywords: Family support, Intention, Stop Smoking, Active smoker.